Test Method for Dynamic Flexibility of Large Thread Pitch Turning - LI Zhe; LI Jingshuai; FU Xiangfu; LI Junwei; WANG Xiurui; ZHOU Yadong (Journal of Harbin University of Science and Technology)
In the finishing process of turning large pitch thread, the system vibration causes the instantaneous change of the contact relationship between the tool and workpiece The axial change of the tool and workpiece contact relationship causes the thickness of the cutting layer to change, which is the cause of the instantaneous cutting force In this paper, the ratio between vibration displacement and instantaneous cutting force is used to describe the dynamic flexibility of the cutting system and characterize the stability of the large pitch thread system The vibration and cutting force signals are processed by using wavelet packet decomposition and reconstruction, wavelet packet denoising and curve fitting The method for obtaining the dynamic flexibility of the cutting system can quickly and accurately represent the relationship between the vibration displacement and the instantaneous cutting force, and judge the system stability in the cutting stroke